Purification of lipopeptide biosurfactant extracts obtained from a complex residual food stream using Tricine-SDS-PAGE electrophoresis - Moldes, A. B.; Álvarez-Chaver, P.; Vecino, X.; Cruz, J. M. (Frontiers in Bioengineering and Biotechnology, 2023)
Protocols to identify lipopeptide biosurfactant extracts contained in complex residual streams are very important, as fermented agri-food matrices are potential sources of these valuable compounds. For instance, corn steep liquor (CSL), a secondary stream of the corn wet-milling industry, is composed of a mixture of microbial metabolites, produced during the corn steeping process, and other natural metabolites released from corn, that can interfere with the purification and analysis of lipopeptides. Electrophoresis could be an interesting technique for the purification and further characterization of lipopeptide biosurfactant extracts contained in secondary residual streams like CSL, but there is little existing literature about it. It is necessary to consider that lipopeptide biosurfactants, like Surfactin, usually are substances that are poorly soluble in water at acidic or neutral pH, forming micelles what can inhibit their separation by electrophoresis. In this work, two lipopeptide biosurfactant extracts obtained directly from CSL, after liquid–liquid extraction with chloroform or ethyl acetate, were purified by applying a second liquid extraction with ethanol and subsequent removal of non-ethanol-soluble compounds by centrifugation. Following that, ethanolic biosurfactant extracts were subjected to electrophoresis under different conditions. Lipopeptides on Tricine-SDS-PAGE (polyacrylamide gels) were better visualized and identified by fluorescence using SYPRO Ruby dye than using Coomassie blue dye. Sequential extraction with chloroform and ethanol prior to electrophoresis and matrix-assisted laser desorption/ionization (MALDI-TOF-MS) was selected as the best option for purifying lipopeptide biosurfactants.